Hsp27 (HSPB1): a possible surrogate molecular marker for loss of heterozygosity (LOH) of chromosome 1p in oligodendrogliomas but not in astrocytomas - Castro, Gisela Natalia (2012)
In oligodendrogliomas, 1p loss of heterozygosity (LOH) is a predictor of good prognosis and treatment response. In contrast, in uveal melanomas, LOH of chromosome 3 has been linked to poor prognosis and downregulation of Hsp27. In the present study, we have analyzed the expression of heat-shock proteins (Hsps) to characterize subtypes of gliomas and their histopathologic features and to correlate with other molecular markers including LOH of 1p. Biopsies from patients with primary gliomas (n = 65) were analyzed by immunohistochemistry, chromogenic in situ hybridization and fluorescent in situ hybridization and methylation-specific PCR (MSP). Elevated Hsp27 and total Hsp70 expression levels were associated with high-grade astrocytomas (p = 0.0001 and p = 0.01, respectively). In grade III oligodendrogliomas, the Hsp27 levels were significantly higher (p = 0.03). Low O6-methylguanine-DNA methyltransferase (MGMT) expression was associated with grade II astrocytomas. Elevated β-catenin expression was associated with grade III/IV astrocytomas (p = 0.003); p53 (+) tumors were more frequently found in grade III/IV astrocytomas (p = 0,001). LOH on 1p was associated with oligodendroglial tumours. In addition, a higher Hsp27 expression correlated with LOH of 1p (p = 0.017); this was also tested in two glioma cell lines. MSP was successful in only six samples. No significant correlations were found for the other markers. In conclusion, in oligodendroglial tumors, Hsp27 appeared as a surrogate marker of LOH of 1p which could also help to predict the disease prognosis. In gliomas, p53, Hsp27, Hsp70, MGMT, and β-catenin correlated with histopathological characteristics, suggesting that these markers could predict the disease outcome and the response to treatments.